Impact of age on the performance of the ESC 0/1h-algorithms for early diagnosis of myocardial infarction - Boeddinghaus, Jasper; Giannitsis, Evangelos (European heart journal, 2018)
AbstractAims. We aimed to evaluate the impact of age on the performance of the European Society of Cardiology (ESC) 0/1h-algorithms and to derive and externall